Characterization, source identification and risk associated with polyaromatic and chlorinated organic contaminants (PAHs, PCBs, PCBzs and OCPs) in the surface sediments of Hooghly estuary, India. (April 2019) - Mitra, Soumita; Corsolini, Simonetta; Pozo, Karla; Audy, Ondrej; Sarkar, Santosh Kumar; Biswas, Jayanta Kumar
Abstract: The spatial distribution, source identification and ecotoxicological impact of a group of persistent organic pollutants (POPs: dichlorodiphenyltrichloroethane (DDT), hexachlorocyclohexanes (HCHs), polychlorobiphenyls (PCBs), polychlorobenzenes (PCBzs)), and polyaromatic hydrocarbons (PAHs) were investigated in surface sediment samples (0–5 cm, <63 μm grain size) along the ecologically stressed Hooghly River estuary, East India. The results demonstrated a wide range of concentrations (ng/g dry weight) with the following decreasing order: ∑16 PAHs (3.3–630) > ∑6 DDTs (0.14–18.6) > ∑7 PCBs (0.28–7.7) > ∑2 PCBzs (0.01–1.3) > ∑5 HCH (0.10–0.6), with a dominance of p, p ′-DDT and higher molecular weight PAHs. Selected diagnostic ratios indicated a mixture of both pyrolytic and petrogenic sources of PAHs, inputs of weathered DDT and their degradation in oxidizing environment, and a predominance of industrial input over the agricultural wastes. The cumulative impact of the pollutants (effective range medium quotient (ERMq): 0.01–0.16) reflected minimal to low ecotoxicological risk, with highest probability of toxic effects towards surrounding biota at Barrackpore (21%). ∑6 DDTs exceeded the effect range low value resulting occasional adverse impact to the sediment dwelling organisms. Among the PAHs, the 4-ringed compounds accounted for 68% of the PAHs. Further, carcinogenic PAHs (BaA, Chry, BbF, BkF, BaP, DahP, Inp) possessed highest cancer risk (CR = 2.09 × 10 −3 ) to the local population when exposed to the sediments from the studied area and ingestion was found to be the primary process of contamination. The study strongly recommends a systematic monitoring of POPs and PAHs, being the Hooghly River water used by local people for their livelihood. Highlights: High exposure through ingestion suggests higher risk due to biomagnification. PAH sources were both from pyrolytic and petrogenic origins together. PAH carcinogenic potential were lower than other Indian and Asian river estuaries. p, pʹ -DDE and o, pʹ -DDT exceeded the average global concentration. α-HCH/γ-HCH indicated sources from lindane and HCH technical mixtures.